Model Optimalisasi Iklan Digital dalam Meningkatkan Daya Saing Usaha Mikro Kecil dan Menengah pada UMKM Cume Yume - Rizky Ayu Andini; Raissa Dea Fernanda; Kurnia Sukma Adriyani; Jenifer Fiorentina Prasanti; Aprilia Paramadina (Journal of Community Service and Engagement, 2026)
The development of digital technology has opened up great opportunities for MSMEs to increase their competitiveness through the use of digital technology. However, there are still many MSMEs that are unable to manage digital advertising optimally, including in content planning and target determination. This community service activity aims to increase the understanding and skills of Cume Yume MSMEs in optimizing digital advertising as a marketing communication strategy. The results of this activity show a significant improvement in digital advertising performance, as indicated by an increase in the number of views, reach, interactions, and followers of Cume Yume SME’s social media accounts. In addition, partners showed changes in digital marketing management by starting to utilize ad insight data as a basis for determining marketing strategies. This activity provides concrete support for SME empowerment efforts through the sustainable optimization of digital advertising.